An exploration of intelligence management opportunities for organizations in the UAE: Possible challenges for culture - BAHERMEZ, ABDULLA OMAR (2017)
The aim of this paper was to explore the intelligence management opportunities available to Organizations operating within the UAE market, and the likely impact of the UAE culture on Such businesses. Business intelligence is a crucial component of a firm’s intelligence Management process. It also influences the competitive intelligence process. The study adopted a Constructivist qualitative approach to understand the challenges faced by organizations in the UAE market in implementing intelligence management processes. A deductive research Approach was deemed ideal in understanding the concept of intelligence management as it affects Businesses in the UAE. A descriptive research design aided in obtaining in-depth knowledge on The application of intelligence management by businesses in the UAE. Data collection was Accomplished. Via the use of an online survey administered to business managers in the UAE. Study findings revealed that technology, emotional intelligence and consumer preferences all Influence business intelligence. Consequently, these factors act as an opportunity for firms in the UAE to exploit, thereby enabling them to easily integrate these with their business intelligence Management systems. The findings further show that integrating efficiency and flexibility enable Businesses to apply business intelligence and thus equip them with a competitive advantage in The UAE market. Moreover, study findings revealed that cultural diversity has a positive impact On the implementation of business intelligence, as does cohesive culture. The study identified Business intelligence as vital component in enhancing emotional intelligence, promoting social Cohesion, increasing understanding of customer preferences, and promoting business Technological capabilities. The use of business intelligence in data collection promotes Competitiveness and knowledge acquisition, while proper management of business intelligence Enables a firm to keep a close eye on the competition. Effective national culture is positively Linked to business intelligence. Besides, business intelligence enables organizations in the UAE To gain useful insights on consumer behavior. Such information aids in the development of Products and services that match consumer preferences.